Environmental preservation and the Grey Cliffs conflict : negotiating common narratives, values, and ethos - Pickering, Kristin D. (Utah State University Press, 2024)
"A qualitative, ethnographic, observational case study approach presenting an analysis of the process of conflict negotiation between an Army Corps of Engineers Resource Manager and a community as they struggle to address a deteriorating, Corps-managed recreational lake area"--